Rebalancing agents in hemophilia: knowns, unknowns, and uncertainties - Quentin Van Thillo; Cédric Hermans (Haematologica)
Treatment options for patients with hemophilia and other bleeding disorders have advanced dramatically over the last few years, not only with the availability of safer factor concentrates, but also with the introduction of factor VIII-mimicking agents. Until recently, there were still areas of hemophilia care that required attention and optimization, including the need of repeated venipuncture, often requiring a central venous access device, and the possible development of inhibitors that limit the efficacy of factor replacement, thereby increasing the complexity and burden of therapy. A new class of rebalancing agents aims to address these remaining issues by inhibiting various natural anticoagulants. Fitusiran is a small interfering RNA agent that reduces antithrombin synthesis in hepatocytes, favoring a procoagulant state. Other promising rebalancing agents are concizumab and marstacimab, which selectively bind to the K2 domain of the tissue factor pathway inhibitor, thus restoring thrombin generation. SerpinPC is a subcutaneous biological inhibitor that blocks the anticoagulant activated protein C pathway, while VGA039 is a monoclonal antibody that targets its cofactor protein S. Although the available clinical data are promising, several important challenges remain. These include the thrombotic risk of rebalancing agents, perioperative and bleeding management, availability in low-income countries, efficacy and FVIII equivalence compared to existing treatments, ideal target populations, and potential application in other hemostatic disorders. The primary aim of this review is to summarize the best available evidence on these novel rebalancing agents, while highlighting the unknowns, and emphasizing the uncertainties that lie ahead.